2005
DOI: 10.1089/pho.2005.23.399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nd:YAG Laser Irradiation on Root Canal Dentin Wall: A Scanning Electron Microscopic Study

Abstract: Objective: The purpose of this study was to evaluate, by scanning electron microscopy (SEM), the effects of Nd:YAG laser irradiation applied perpendicular or parallel to the root canal dentin wall. Methods: Thirty human teeth were divided into two groups: Group A (20 roots), laser application with circular movements, parallel to the dentin root surface; and Group B (10 roots), roots cut longitudinally and laser applied perpendicular to the root surface. Group A was subdivided into A1 (10 roots), laser applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 21 publications
(65 reference statements)
0
19
0
10
Order By: Relevance
“…Several studies demonstrated its efficacy in cleanliness and disinfection. 8,9,[11][12][13][14][15] Few studies have compared the resin-based sealers that were investigated in the present study and the influence of high-intensity laser irradiation on the adaptation and penetration into dentin tubules of these sealers. 3,5,6 Therefore, the hypothesis of this study is that the treatment of dentin prior to obturation using high intensity laser irradiation interferes with the quality of the apical seal when using resin-based sealers was accepted.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies demonstrated its efficacy in cleanliness and disinfection. 8,9,[11][12][13][14][15] Few studies have compared the resin-based sealers that were investigated in the present study and the influence of high-intensity laser irradiation on the adaptation and penetration into dentin tubules of these sealers. 3,5,6 Therefore, the hypothesis of this study is that the treatment of dentin prior to obturation using high intensity laser irradiation interferes with the quality of the apical seal when using resin-based sealers was accepted.…”
Section: Discussionmentioning
confidence: 99%
“…These results concur with other reports in the literature. 9,[15][16][17][18][19] On the other hand, Er: YAG laser irradiation caused ablation of the dentin surface, which was more evident in the intertubular than the peritubular dentin. This resulted in more exposed dentinal tubules as previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations